LANDSLIDES IN THE CITY OF MILA BETWEEN THE SENSITIVITY OF THE LOCATION AND URBAN EXPANSION - Bouguerroudja Nassima; Amirech Hamza (International Journal of Innovative Technologies in Social Science, 2024)
Cities are evolving rapidly, exposing them to natural hazards that can cause major human and environmental losses. The Algerian town of Mila is particularly vulnerable due to its complex geological and morphological environment, which favours various risks, such as landslides. The aim of this article is to highlight the risk of landslides in Mila, particularly in the Khirbet region. To analyse these risks, it is essential to define concepts such as natural risks, high risks, Algerian risks, the phenomenon, vulnerability and prevention. High risks are physical phenomena caused by fast- or slow-moving phenomena, while high risks are potential threats caused by exceptional natural or human activities. Vulnerability refers to the ability to withstand losses resulting from exposed areas and the fragility of the situation. Understanding and dealing with natural hazards in urban environments is crucial for sustainable development, preserving the urban environment and protecting citizens. The study revealed that natural factors, such as topography, geology, seismic activity and hydrology, play an important role The report recommends greater coordination between institutions and citizens, better knowledge of landslide risks, early warning systems and increased funding for disaster risk reduction and mitigation. Comprehensive and integrated approaches are needed to tackle climate and disaster challenges in Algeria. ground movements in Mila The report recommends greater coordination between institutions and citizens, better knowledge of landslide risks, early warning systems and increased funding for disaster risk reduction and mitigation. Comprehensive and integrated approaches needed to tackle climate and disaster challenges in Algeria.